Preventive Home Visits - Norman Bannenberg; Oddvar Førland; Tor Iversen; Martin Karlsson; Henning Øien (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2019)
This paper evaluates the introduction of preventive home visits (PHV) for older people in Norway. Their purpose is to support autonomy and independence as well as preventing disability and nursing home admissions. We contribute to the literature by exploiting a natural experiment in Norwegian municipalities. Our results show that the introduction of a PHV program significantly changes the use of local public resources away from nursing homes, while increasing the utilization of home-based care. Further, PHVs lead to a decline in hospital admissions by 8 percent – whereas treatments for mental health conditions remain unaffected. Mortality is reduced by 4 percent in the age group 80 and above.
Keywords: C23; H75; I18; J14; J18; 330; preventive home visits; long-term care; natural experiment; primary prevention